Potential Model to Support the Achievement of Corporate Carbon Neutrality - Bognár, Ferenc; Böcskei, Elvira (Public Finance Quarterly, 2022)
In our article, based on the methodology of internationally known sustainability models, we propose developing a novel, decision support and controlling system to motivate organizations to achieve net zero emissions. The evaluation system fits the GHG Protocol’s criteria, considers the emissions of all three Scopes, and provides the opportunity for benchmarking and stress testing. The model supports the management’s decisions visually, and it also offers regulators the opportunity to prepare and make industry level decisions. The creation of the new model is especially necessary in a period fraught with geopolitical tensions, when the price and availability of individual energy carriers can change dramatically and rapidly.